MR1 blockade drives differential impact on integrative signatures based on circuits of circulating immune cells and soluble mediators in visceral leishmaniasis - Luana Oliveira Borges-Fernandes; Marcela de Lima Moreira; Victória Hellena Silva Pereira; Marcelo Antônio Pascoal-Xavier; Marcelo Antônio Pascoal-Xavier; Ágata Lopes Ribeiro; Ágata Lopes Ribeiro; Ismael Artur da Costa-Rocha; Ludmila Rosa Lopes; Guilherme Telles Cristo Moreira; Márcio Sobreira da Silva Araújo; Andréa Teixeira-Carvalho; et al. (Frontiers in Immunology, 2024)
IntroductionVisceral leishmaniasis (VL) is an important tropical and neglected disease and represents a serious global health problem. The initial interaction between the phagocytes and the parasite is crucial to determine the pathogen’s capacity to initiate infection and it shapes the subsequent immune response that will develop. While type-1 T-cells induce IL-6, IL-1β, TNF-α, and IL-12 production by monocytes/macrophages to fight the infection, type-2 T-cells are associated with a regulatory phenotype (IL-10 and TGF-β) and successful infection establishment. Recently, our group demonstrated the role of an important Th1/Th17 T-cell population, the mucosal-associated invariant T (MAIT) cells, in VL. MAIT cells can respond to L. infantum by producing TNF-α and IFN-γ upon MR1-dependent activation.Objective and methodsHere, we describe the impact of the MR1-blockage on L. infantum internalization on the functional profile of circulating neutrophils and monocytes as well as the impact of the MR1-blockage on the soluble mediator signatures of in vitro whole blood cultures.ResultsOverall, our data showed that VL patients presents higher percentage of activated neutrophils than asymptomatic and non-infected controls. In addition, MR1 blockade led to lower TNF-α and TGF-β production by non-activated neutrophils from asymptomatic individuals. Moreover, TNF-α and IL-10 production by monocytes was higher in VL patients. In the analysis of soluble mediators produced in vitro, MR1-blockade induced a decrease of IFN-γ and an increase of IL-10, IL-27 and IL-33 in the cell cultures of AS group, a cytokine pattern associated with type 2 deleterious response.Discussion and conclusionThese data corroborate the hypothesis that MR1-restricted responses are associated to a protective role during Leishmania infection.